Food availability and affordability in a Mediterranean urban context: associations by store type and area-level socio-economic status - Carlos Fernández-Escobar; Julia Díez; Alba Martínez-García; Usama Bilal; Martin O'Flaherty; Manuel Franco (Cambridge University Press, 2023)
Abstract Objective: Although food environments have been highlighted as potentially effective targets to improve population diets, evidence on Mediterranean food environments is lacking. We examined differences in food availability and affordability in Madrid (Spain) by store type and area-level socio-economic status (SES). Design: Cross-sectional study. Trained researchers conducted food store audits using the validated Nutrition Environment Measures Survey in Stores for Mediterranean contexts (NEMS-S-MED) tool to measure the availability and price of twelve food groups (specific foods = 35). We computed NEMS-S-MED scores and summarised price data with a Relative Price Index (RPI, comparing prices across stores) and an Affordability Index (normalising prices by area-level income). We compared the availability and affordability of 'healthier-less healthy' food pairs, scores between food store types (supermarkets, specialised, convenience stores and others) and area-level SES using ANOVA and multi-level regression models. Setting: City of Madrid. 2016 and 2019 to cover a representative sample. Participants: Food stores within a socio-economically diverse sample of sixty-three census tracts (n 151). Results: Supermarkets had higher food availability (37·5/49 NEMS-S-MED points), compared to convenience stores (13·5/49) and specialised stores (8/49). Supermarkets offered lower prices (RPI: 0·83) than specialised stores (RPI: 0·97) and convenience stores (RPI: 2·06). Both 'healthy' and 'less healthy' items were more available in supermarkets. We found no differences in food availability or price by area-level SES, but affordability was higher in higher-income areas. Conclusions: Supermarkets offered higher food availability and affordability for healthy and less healthy food items. Promoting healthy food availability through supermarkets and specialised stores and/or limiting access to convenience stores are promising policy options to achieve a healthier food environment.